QR code based queueing assistance in Android - Heng, Zhi Guang (2019)
Quezee is a powerful Android application that utilize QR code to generate a queue number for customer in the restaurant. Live updates of queue status are provided to customer. Quezee allow customer to view the menus, order menus and make payment. This project aims to build a smartphone application in Android to facilitate the queueing process by using the QR code as an assistance. The objective is to release the people from the pain of queueing and still guarantee the fairness through technology.